PENGARUH NITROCARBURIZING TERHADAP KEKERASAN, STRUKTUR MIKRO DAN LAJU KOROSI PADA BAJA TAHAN KARAT AISI 410 - , EDY IRYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
AISI 410 stainless steel is one of the stainless steels that are widely used in medical. Improvement of mechanical properties of martensitic stainless steels can be done by means of surface hardening. Various surface engineering technologies have been developed to increase the hardness, one of which is nitrocarburizing. This research was conducted to study the effect of process variations on time nitrocarburizing stainless steel AISI 410 on hardness, microstructure and corrosion rate. Specimens were made with a cylindrical shape with a diameter of 14 mm and a thickness of 3 mm. Specimens that have been smoothed and polished surface, nitrocarburized at a temperature of 400 Â° C with the variation of time 2, 3, 4, 5 and 6 hours, at a constant pressure of 1.6 mbar, in a mixed environment of Methane, Hydrogen and Nitrogen with a weight ratio : 3.08 % CH4, 19.31 % H2, and balance N2. The method used is a plasma glow discharge, which will cause the ions of N and C will be deposited into the surface of the specimen. Nitrocarburized specimens are hardness tested with microhardness tester and observed with a microscope to see the microstructure. Specimens were also tested with a galvanostat corrosion, corrosion test equipment type three-electrode cell, with a 0.9% NaCl media. The results of this study indicate that the AISI 410 stainless steel specimens with nitrocarburizing treatment for 5 hours had the highest of hardness, which is 368 VHN. When compared to hardness of raw material, ie 210.2 VHN, then there is an increase of 175% of hardness. The test results do not show the microstructure changes significantly. Corrosion test results show the corrosion rate of raw material is 0.2998 mpy, while the corrosion rate of AISI 410 stainless steel that is nitrocarburized at 400 o C, pressure of 1.6 mbar with a time of 6 hours is 0.2467 mpy. Itâs Outstanding, because the corrosion rate < 1 mpy.